Exploring factors affecting employee loyalty at PT. Panca Tehnik Banjar Regency - Agustina, Dhea Ananda; Nastiti, Rizky; Wahdah, Rofiqah; Daud, Ibrahim (Junal Ilmu Manajemen, 2025)
Understanding the key elements that contribute to employee commitment will enable the company to identify the most influential aspects in fostering long-term organizational loyalty. Thus, this study aims to explore the factors influencing employee loyalty at PT Panca Tehnik, Banjar Regency, with a focus on compensation, work commitment, and work communication. Employee loyalty is a critical aspect of organizational success, particularly in industries characterized by rapid change and high competition. PT Panca Tehnik, a company operating in the service and production sectors, has demonstrated a notable level of employee retention, suggesting the presence of internal factors that foster long-term commitment. Through a quantitative approach, this research examines the extent to which compensation, work commitment, and work communication contribute to employee loyalty. Data for this study were collected through the distribution of questionnaires to a sample of 73 respondents, determined using the Slovin formula. The findings reveal that all three variables have a positive effect on employee loyalty, either partially or simultaneously. However, the analysis indicates that the influence of work commitment and work communication on employee loyalty is not statistically significant. Competitive compensation enhances employees' sense of value and satisfaction, strong work commitment reflects emotional attachment and responsibility toward the company, and effective work communication fosters trust, transparency, and collaboration. This study not only provides strategic insights for PT Panca Tehnik in strengthening employee retention policies but also contributes to the broader literature on human resource management by highlighting key drivers of employee loyalty in the industrial services sector.